ANALISIS PEMAHAMAN KONSEP PADA MATERI PERKALIAN ALJABAR DITINJAU DARI KESALAHAN SISWA BERDASAR PROSEDUR NEWMAN - Anjarwati Anjarwati; Hartono Hartono (Mandalika Mathematics and Educations Journal, 2026)
This study is motivated by students' low ability to receive and process problem information, making error analysis necessary to understand conceptual understanding and help teachers determine appropriate learning strategies. The study aims to describe students' conceptual understanding in algebraic multiplication material, analyze the relationship between student errors based on Newman's procedure, and develop learning recommendations. The research employed a descriptive approach combining quantitative and qualitative analysis, with 30 seventh-grade students at a junior high school in Yogyakarta as subjects. Data were collected through conceptual understanding tests, analyzed quantitatively through descriptive statistics in the form of scores and categories, and qualitatively to identify student errors using five Newman stages: Reading Error, Comprehension, Transformation, Process Skill, and Encoding. Results indicate that students' conceptual understanding falls in the fairly good category with an average score of 79.72, with the highest indicator on connect knowledge and the lowest on evaluate thinking and purpose ideas and conjecture. Errors in reading and understanding problems indicate weak conceptual understanding, whereas the ability to construct procedures and write correct answers reflects strong conceptual understanding. Learning recommendations emphasize strengthening basic concepts, complete solution procedures, and developing students' evaluation skills and mathematical idea expression.